The anthropology of Ireland - Wilson, Thomas M., 1951- (Berg, 2006)
Where and what is Ireland? What are the identities of the people of Ireland? How has European Union membership shaped Irish people's lives and interests? And how global is local Ireland? This book argues that such questions can be answered only by understanding everyday aspects of Irish culture and identity. Please note that images or diagrams have been excluded from this text due to copyright restrictions.